2014
DOI: 10.1016/j.jinsphys.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, depletion and cell-type expression of a protein from the male accessory glands of the dengue vector mosquito Aedes aegypti

Abstract: Aedes aegypti males transfer sperm and seminal fluid proteins (Sfps), primarily produced by male accessory glands (AGs), to females during mating. When collectively injected or transplanted into females, AG tissues and/or seminal fluid homogenates have profound effects on Aedes female physiology and behavior. To identify targets and design new strategies for vector control, it is important to understand the biology of the AGs. Thus, we examined characteristics of AG secretion and development in Ae. aegypti, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 38 publications
0
33
0
1
Order By: Relevance
“…Because the UPR is so well conserved, our approach can be extended to impair accessory gland function in other insects, if an AG-specific promoter (e.g. in Aedes aegypti [ 37 ]) is available to drive expression of the misfolded protein. Thus, this may provide a general method applicable to the control of fertility of insect vectors of human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Because the UPR is so well conserved, our approach can be extended to impair accessory gland function in other insects, if an AG-specific promoter (e.g. in Aedes aegypti [ 37 ]) is available to drive expression of the misfolded protein. Thus, this may provide a general method applicable to the control of fertility of insect vectors of human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that Ae. 203 aegypti males become depleted after mating with three to five females in succession, and 204 seminal fluid is slowly regenerated over 48 h [46]. In our study, we provided males with 205 four virgin females for a period of 8 h to allow for male seminal fluid depletion.…”
Section: /30mentioning
confidence: 94%
“…Interestingly these vesicles, which may carry 715 RNA cargo including miRNAs, fuse with sperm and have the capacity to interact with 716 the female reproductive tract. Some male-derived transcripts are detectable in the 717 female for up to 24 h post-mating [46], and it has been postulated that they could be 718 used by females in some capacity [104]. In Ae.…”
Section: /30mentioning
confidence: 99%
See 1 more Smart Citation
“…During copulation, males are thought to transfer a cocktail of sperm and SFPs, but 533 recent work has shown that males can also transfer mRNAs that can be detected in 534 the female's post-mating transcriptome [35,91]. In both of the reported cases in 535 insects, the mRNAs appear to originate from the male accessory glands as the mRNAs 536 are derived from known SFP genes or show strong expression bias in the accessory 537 glands.…”
mentioning
confidence: 99%